Challenges for the EU as Germany approaches recession - George K. Zestos; Rachel N. Cooke (Levy Economics Institute of Bard College, 2020)
This paper analyzes recent macroeconomic developments in the eurozone, particularly in Germany. Several economic indicators are sending signals of a looming German recession. Geopolitical tensions caused by trade disputes between the United States and China, plus the risk of a disorderly Brexit, began disrupting the global supply chain in manufacturing. German output contraction has been centered on manufacturing, particularly the automobile sector. Despite circumstances that call for fiscal intervention to rescue the economy, Chancellor Angela Merkel's government was overdue with corrective measures. This paper explains Germany's hesitancy to protect its economy, which has been based on a political and historical ideology that that rejects issuing new public debt to increase public spending, thus leaving the economy exposed to the doldrums. The paper also considers serious shortcomings in the European Union's (EU) foreign and defense policies that recently surfaced during the Syrian refugee crisis. The eurocrisis revealed near-fatal weaknesses of the European Monetary Union (EMU), which is still incomplete without a common fiscal policy, a common budget, and a banking union. Unless corrected, such deficiencies will cause both the EU and the EMU to dissolve if another asymmetric shock occurs. This paper also analyzes recent geopolitical developments that are crucial to the EU/eurozone's existential crisis.
Keywords: B22; E50; E60; F02; F15; F45; H30; H60; 330; Balanced Budget; Fiscal Stimulus; Debt Brake; Recession; Austerity; Geopolitical Tensions; Syria; Libya